Aloe burgersfortensis (Asphodelaceae subfam. Alooideae): a distinctive, winter-flowering maculate aloe endemic to the southeastern Limpopo and northwestern Mpumalanga provinces of South Africa - Smith, Gideon F.; Figueiredo, Estrela; Klopper, Ronell R. (Phytotaxa, 2024)
Aloe burgersfortensis (Asphodelaceae subfam. Alooideae), which generally has been included in the synonymy of A. parvibracteata since 2000, is formally reinstated as an accepted species that is endemic to the southeastern Limpopo and northwestern Mpumalanga provinces of South Africa. Aloe burgersfortensis differs from A. parvibracteata in several vegetative and reproductive morphological characters so warranting its recognition at the rank of species; the differences are quantified and discussed. The typification of the name A. burgersfortensis is reinterpreted and corrected. Both A. burgersfortensis and A. parvibracteata are illustrated and an amplified description is provided for A. burgersfortensis.